First medical contact facility type as a determinant of prognosis in a regional ST elevation myocardial infarction network. (3rd October 2022) - De Diego Soler, O; Garcia-Garcia, C; Rueda, F; Carrillo, X; Andrea, R; Regueiro, A; Mauri, F; Lidon, R M; Tizon, H; Garcia-Pitarch, J; Bayes-Genis, A
Abstract: Background: Delay in primary percutaneous coronary intervention (PPCI) in ST elevation myocardial infartion (STEMI) is associated with worse prognosis. In our regional STEMI network, the first medical contact (FMC) facility type defines 4 different assistance pathways (i.e. emergency medical services'diagnosis on the field and direct transfer to the catheterization laboratory (cath. lab) of a PCI hospital (EMS group); direct admission to a PCI hospital (PCI-H group); admission to community hospital and transfer to the cath lab of the PCI-H (CH group); diagnosis in a primary care centre and transfer to the cath lab of the PCI-H (PCC group). Each different FMC has been associated with different degrees in reperfusion delay. Objective: To determine the influence of FMC facility type on 1-year mortality in patients with STEMI in our regional STEMI network. Methods: This is a retrospective study based on the STEMI network registry, a mandatory registry conducted since its implantation and supervised by the regional health authorities. We included STEMI patients treated with PPCI from January 2010 to December 2020. We analyzed differences in clinical variables, reprefusion times and 1-year all-cause mortality regarding the FMC facility type. Results: We included 18332 patients (EMS 34.25%, PCI-H 12.28%, CH 33.47%, PCC 20.01%). Initial Killip classes III–IV: EMS 8.43%, PCI-H 7.51%, CH 5.54%, PCC 3.76%; p<0.001. All comorbidities and complications in first medical assistance were more frequent in EMS and PCI-H groups (p<0.05). PCC group had the lowest risk profile regarding comorbidities and first medical assistance complications (p<0.05 for most of variables). The PCI-H group had the shortest system delay (median 82 min, p<0.001), the EMS group had the shortest total ischemic time (median 151 min, p<0.001). Crude 1-year mortality was EMS 8.6%, PCI-H 9.11%, CH 8.25%, and PCC 4.77% (p<0.001). After adjusting for several covariables with a logistic regression model, PCI-H and CH groups were associated with higher 1-year mortality compared to EMS group (OR 1.23 (IC95% 1.01–1.49; p=0.04) and OR 1.16 (IC95% 1.01–1.34; p=0.04) respectively), while PCC group was associated with lower 1-year mortality (OR 0.69 (IC95% 0.57–0.84; p<0.01)). Conclusions: First medical contact with EMS and direct transfer to the cath lab was associated with lower adjusted 1-year mortality compared to first medical contact with a PCI hospital or a community hospital. Funding Acknowledgement: Type of funding sources: None.